Essentials of school neuropsychological assessment - Miller, Daniel C. (Daniel Carlton), 1956-; Maricle, Denise E. (Essentials of psychological assessment series., 2019)
"The Third Edition of Essentials of School Neuropsychological Assessment provides a current, concise overview of all aspects of neuropsychological practice in schools and explains how to identify the need for testing, how to collect a neurodevelopmental history, select appropriate assessment instruments, effectively evaluate students, and accurately interpret results. Appropriate for school psychologists and other mental health professionals who work with children, this important, useful resource: Provides a comprehensive conceptual model that can be used as a guide for conducting school neuropsychological assessments; Includes numerous case studies, practice examples, and new tips for report writing; Offers new coverage of major neuropsychological test batteries for children, including NEPSY-II, Wechsler Intelligence Scale for Children, Fourth Edition integrated, and Delis-Kaplan Executive Function System; Features numerous callout boxes highlighting key concepts, bulleted points, and extensive illustrative material, as well as test questions that help gauge and reinforce your grasp on the information covered * New DSM-V references; Updated tools now online, including sample case studies, searchable databases of neuropsychological tests classified by processing area and conceptual model, a neuropsychological processing concerns checklist in both English and Spanish, and sample report shells with tables;"--